TRENDS IN THE DEVELOPMENT OF DIGITAL TECHNOLOGIES - Qosimjonova Gulzira (Лучшие интеллектуальные исследования, 2024)
Abstract: This article discusses the development stages and trends of digital technologies. Historical documents and evidence were used in the discussion.